2018
DOI: 10.1111/omi.12227
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal infection with Porphyromonas gingivalis induces preterm birth and lower birth weight in rats

Abstract: Preterm birth (PTB), accompanied by low birth weight (LBW) or not, is a syndrome with tremendous risk factors and long-term health consequences for children. In recent decades, overwhelming studies have shown that periodontitis contributes to prematurity and LBW. This study was conducted to determine the link between maternal periodontitis and the pathogenesis of PTB and/or LBW through a rat infection model induced by Porphyromonas gingivalis, an important periodontopathic bacterium. The murine model was estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
3
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 53 publications
2
18
3
5
Order By: Relevance
“…Herein we report that P. gingivalis infection induced ISAR in both rat strains, but only infected WIS dams exhibited FGR. In contrast to other studies 10,15 , neither maternal systemic inflammation nor placental (fetal) inflammation was a feature of FGR. In addition, placental microbial load was equivalent in both rat strains suggesting this was not a determining factor in the development of FGR.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Herein we report that P. gingivalis infection induced ISAR in both rat strains, but only infected WIS dams exhibited FGR. In contrast to other studies 10,15 , neither maternal systemic inflammation nor placental (fetal) inflammation was a feature of FGR. In addition, placental microbial load was equivalent in both rat strains suggesting this was not a determining factor in the development of FGR.…”
contrasting
confidence: 99%
“…Using a rodent model of infection, we previously demonstrated that P. gingivalis disrupts the physiologic remodeling of the uterine spiral arteries during pregnancy 11 , providing a common mechanistic model for how this microbe could contribute to a wide array of pregnancy disorders. One unexpected outcome from that study was the lack of FGR with P. gingivalis infection 11 even though FGR can be an outcome of infection 10,[13][14][15]45 as well as a complication of ISAR 34 . Given that different rat strains show varying susceptibility to infection and injury [46][47][48] , we originally postulated that P. gingivalis-induced FGR was a rat strain dependent phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest the involvement of P. gingivalis in APOs through direct invasion and damage to utero-placental tissues. Subsequently, various rodent models confirmed that P. gingivalis infection can induce diverse utero-placental pathologies (such as endometrial arteritis, mild chorioamnionitis, and utero-placental hemorrhage with structural disorder of placenta) and cause a diverse array of APOs, including fetal growth restriction (FGR), low birth weight (LBW), and PB [ 137 , 138 , 139 ].…”
Section: Obstetricsmentioning
confidence: 99%
“…The direct dissemination of P. gingivalis to the placenta and its pathogenicity mechanisms have been proposed in many animal experiments. It has been reported that P. gingivalis could translocate to local placental tissues in rats and enhance the expression of Fas, FasL, and TLR2, leading to PB and LBW [ 137 ]. P. gingivalis infection in pregnant mice induced a fetus-specific placental immune response and increased the placental Th1/Th2 cytokine ratio (increased expression of IFN-γ, IL-2, and IL-12, decreased expression of IL-4 and IL-10), which may be related to the occurrence of FGR [ 138 ].…”
Section: Obstetricsmentioning
confidence: 99%